Covalent triazine frameworks for the selective sorption of palladium from highly acidic radioactive liquid wastes. Issue 48 (9th November 2021) - Wu, Pengcheng; Liu, Hui; Sun, Mengqi; Zeng, Yaxin; Ye, Jiawei; Qin, Song; Cai, Yimin; Feng, Wen; Yuan, Lihua
Abstract : Two novel robust covalent triazine frameworks (CTFs) have been prepared, which present excellent irradiation stability, sorption capability, and selectivity for Pd(ii ) at 1–6 M HNO3 with the highest uptake of 333 mg g −1 at 3 M HNO3 . Abstract : Efficient palladium recovery from high level liquid wastes (HLLW) is of increasing priority for sustainable development and addressing issues in radioactive waste treatment. However, searching for robust materials for palladium sorption, in the presence of large amounts of competing ions even at rather high acidity still poses a great challenge. Herein we present two novel cationic covalent triazine frameworks (denoted as CTF-S and CTF-L) created by polymerization of monomers IL-S and IL-L for palladium recovery. The resultant CTF-S and CTF-L with respective surface areas of 212.9 m 2 g −1 and 342.5 m 2 g −1 exhibit excellent sorption ability toward palladium at high acidity. This has been demonstrated by a maximum sorption capacity of 333 mg g −1, which is the highest at 3 M HNO3 among all porous adsorbents reported so far. More importantly, these materials reveal remarkable selectivity toward palladium over other metal ions that are co-existing in simulated HLLW. In addition, thanks to the relatively large π-conjugated structures, no obvious decrease in sorption capability was observed after being exposed to 1000 kGy γ irradiation. Desorption could be easily achieved by a single contact with a mixed solution of 1 M thiourea and 1 M HCl and the sorption performance still remains at the initial level without conspicuous loss after five cycles. The XPS results, anion competitive experiments, and DFT calculations propose a sorption mechanism in which the anion exchange between anionic Pd complexes and chloride, and the chemical coordination between triazine N and Pd(ii ) work coorperatively to enhance the sorption capacity. This work not only provides a new kind of excellent adsorbent for selective palladium recovery, but also demonstrates a promising approach for constructing robust materials for nuclear waste remediation.